Aplikasi Pupuk Organik Cair Rebung Bambu Terhadap Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis sativus L.) - Rita Elfianis; Rizal Muhaimi; Riska Dian Oktari (UNIVERSITAS LABUHANBATU, 2026)
Cucumber is one of the horticultural crops that provides many benefits. One of the effort to improve cucumber growth and yield is through fertilization. Fertilization can be carried out using either inorganic or organic fertilizers. However, the continuous use of inorganic fertilizers has a negative impact on sustainable agriculture. One natural material that can be utilized as an organic fertilizer is bamboo shoots. This study aimed to determine the best concentration of liquid organic fertilizer made from bamboo shoots for the growth and yield of cucumber plants.The research was conducted from June to August 2024 at the UARDS field of the Faculty of Agriculture and Animal Science, Sultan Syarif Kasim State Islamic University, Riau. The study employed a Completely Randomized Design (CRD) with four treatments of bamboo shoot liquid organic fertilizer concentrations, namely M0: control, M1: 25%, M2: 50%, and M3: 75%. The observed parameters included plant height, flowering age, fruit length, fruit diameter, number of fruits per plant, fruit weight per fruit, fruit weight per plant, wet weight, and dry weight. The results showed that the application of bamboo shoot liquid organic fertilizer had a highly significant effect plant height, flowering age, fruit length, fruit diameter, number of fruits per plant, fruit weight per fruit, fruit weight per plant, wet weight, and dry weight. Liquid organic fertilizer with a concentration of 75% is the best concentration that can provide results comparable to NPK in the parameters of fruit length, fruit weight per fruit and fruit weight per plant of cucumber.